Statistical investigation of the groundwater system in darb el-arbaein, southwestern desert, egypt (2009)
In Darb El Arbaein, the groundwater is the only water resources. The aquifer system starts from Paleozoic-Mesozoic to Upper Cretaceous sandstone rocks. They overlay the basement rocks and the aquifer is confined. In the present research, the performance of the statistical analyses to classify groundwater samples depending on their chemical characters has been tested. The hydrogeological and hydrogeochemical data of 92 groundwater samples was obtained from the GARPAD authority in northern, central, and southern Darb El Arbaein. A robust classification scheme for partitioning groundwater chemistry into homogeneous groups was an important tool for the characterization of Nubian sandstone aquifer. We test the performance of the many available graphical and statistical methodologies used to classify water samples. R-mode, Q-mode, correlation analysis, and principal component analysis were investigated. All the methods were discussed and compared as to their ability to cluster, ease of use, and ease of interpretation. The correlation investigation clarifies the relationship among the lithology, hydrogeology, and anthropogenic. Factor investigation revealed three factors namely; the evaporation process-agriculturalimpact-lithogenic dissolution, the hydrogeological characteristics of the aquifer system, and the surface meteoric water that rechargethe aquifer system. Two main clusters that subdivided into four sub clusters were identified in groundwater system based on hydrogeological and hydrogeochemical data. They reflect the impact of geomedia, hydrogeology, geographic position, and agricultural wastewater. The groundwater is undersaturated with respect to most selected minerals. The groundwater was supersaturated with respect to iron minerals in northern and southern Darb El Arbaein. The partial pressure of CO2 of the groundwater versus saturation index of calcite shows the gradual change in PCO2 from atmospheric to the present aquifer pressures.